2019
DOI: 10.21037/apm.2019.05.02
|View full text |Cite
|
Sign up to set email alerts
|

The impact of non-medical reading on clinician burnout: a national survey of palliative care providers

Abstract: Background: Clinician burnout in hospice and palliative care (HPC) has potentially widespread negative consequences including increased clinical errors, decreased professionalism, decreased staff retention, and decreased empathy. Reading non-medical literature has been associated with increased empathy, but no studies on the effect of reading on burnout have previously been conducted. We wished to assess reading patterns of practicing HPC clinicians and determine associations between non-medical reading and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 42 publications
0
26
0
3
Order By: Relevance
“…Quality of the papers was assessed as ‘fair’ to ‘good’ in 29 papers. 21,28 55 Thirty studies were rated ‘poor’ to ‘fair’. 56 85 Ten studies were intervention studies, the quality of seven of these was assessed between ‘poor’ to ‘fair’.…”
Section: Resultsmentioning
confidence: 99%
“…Quality of the papers was assessed as ‘fair’ to ‘good’ in 29 papers. 21,28 55 Thirty studies were rated ‘poor’ to ‘fair’. 56 85 Ten studies were intervention studies, the quality of seven of these was assessed between ‘poor’ to ‘fair’.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the problem of burnout, Marchalik et al used the two-item Maslach Burnout Inventory [ 10 ] in a survey of hospice and palliative medicine (HPM) providers. The team discovered that in the population of HPM survey respondents, 16.6% met the criteria for high emotional exhaustion (“I feel burned out from my work”) and 6.3% met the criteria for high depersonalization (“I have become more callous toward people since I took this job”) [ 11 ]. In the same study, it was shown that providers without burnout were more likely to be consistent readers of non-medical literature, thus suggesting that engaging with literature of this kind may actually be a protective factor against burnout in HPM providers [ 11 ].…”
Section: Reading To Promote Empathymentioning
confidence: 99%
“…The team discovered that in the population of HPM survey respondents, 16.6% met the criteria for high emotional exhaustion (“I feel burned out from my work”) and 6.3% met the criteria for high depersonalization (“I have become more callous toward people since I took this job”) [ 11 ]. In the same study, it was shown that providers without burnout were more likely to be consistent readers of non-medical literature, thus suggesting that engaging with literature of this kind may actually be a protective factor against burnout in HPM providers [ 11 ]. Given that the main protective effect was observed across the domain of depersonalization, the authors concluded that reading fiction may help to encourage empathy by strengthening Theory of Mind, thereby reducing provider callousness toward patients.…”
Section: Reading To Promote Empathymentioning
confidence: 99%
“…However, evidence from a meta-analysis highlighted only a small negative correlation between work experience and emotional exhaustion [57]. Recently, another study found that years in practice did not distinguish significantly between burnedout and not burned-out specialist palliative care practitioners [58].…”
Section: Plos Onementioning
confidence: 99%